Harmonic Balance Method for Chaotic Dynamics in Fractional-Order Rössler Toroidal System - Huijian Zhu (Discrete Dynamics in Nature and Society)
This paper deals with the problem of determining the conditions under which fractional order Rössler toroidal system can give rise to chaotic behavior. Based on the harmonic balance method, four detailed steps are presented for predicting the existence and the location of chaotic motions. Numerical simulations are performed to verify the theoretical analysis by straightforward computations.